A review of data visualization: opportunities in manufacturing sequence management. - Sackett, Peter J.; Al-Gaylani, M. F.; Tiwari, Ashutosh; Williams, D. (Taylor and Francis, 2006)
Data visualization now benefits from developments in technologies that offer innovative ways of presenting complex data. Potentially these have widespread application in communicating the complex information domains typical of manufacturing sequence management environments for global enterprises. In this paper the authors review the visualization functionalities, techniques and applications reported in literature, map these to manufacturing sequence information presentation requirements and identify the opportunities available and likely development paths. Current leading-edge practice in dynamic updating and communication with suppliers is not being exploited in manufacturing sequence management; it could provide significant benefits to manufacturing business. In the context of global manufacturing operations and broad-based user communities with differing needs served by common data sets, tool functionality is generally ahead of user application.
Keywords: Manufacturing sequence; Data visualization; Global manufacturing